MASKULINISASI IKAN NILA MERAH (Oreochromis sp.) MENGGUNAKAN PROPOLIS YANG DICAMPUR KE DALAM PAKAN BUATAN - Witoko, Pindo; Noor, Nuning Mahmudah; Pramesthye, Errisha Ardhia; Pratama, Rizal Aditia; Aziz, Rahmadi (Politeknik Negeri Lampung, 2024)
Masculinization is one of the efforts to increase the number of male fish by giving treatment to direct the fish to become male. Masculinization was carried out using Propolis Melia at a treatment dose of 2.7 mL/kg feed with 3 replications. The goal is to produce a male sex ratio and the survival of tilapia. With maintenance for 4 weeks with at-satiation feeding. The results of the percentage of male sex with the treatment dose used were 2.7 mL/kg of feed for repetition 1 (80%), repetition 2 (80%) and repetition 3 (85%) and survival rate 100%.